Bridging gap between Theory and Practice - Idrees, Sobia; Shah, Nawroz Bibi Zeenat (International Journal of Endorsing Health Science Research, 2017)
Background: Nurses are facing many challenges in this competitive era in health care settings and the one biggest challenge among the others is application of theoretical concepts into practice. Moreover, the knowledge about nursing theory and its application into clinical practice is the hallmark of evidence-based practice which is the focus of today’s health care environment. Method: A clinical scenario has been analyzed in the light of Nightingales’ theory. Based on the analysis of application of theory into clinical scenario, few recommendations have been set forth to be implemented for better outcomes of health and speedy recovery from illness with minimum risks. Results: A detailed analysis of clinical scenario showed explicit gap between actual practice and Nightingales’ theory. Conclusion: Florence Nightingale is regarded as a pioneer in the nursing profession. Nightingale has given her notes on nursing in the form of theory of environment which is very useful for nurses to apply those concepts into clinical practice in order to improve health care standards. Application of theoretical concepts in clinical practice would not only improve health outcomes but also minimizes risks and complications.